Inclusive Education: Survey on Teachers' Perception of Its Implementation - Padmadewi, Ni Nyoman; Sukadana, I Made Sukma Adisetiawan; Artini, Luh Putu; Ana, I Ketut Trika Adi; Lesmana, Kadek Yogi Parta; Susiani, Ketut (Universitas Pendidikan Ganesha, 2024)
Inclusive education is still something new in Indonesia's education system. Teachers have an essential role in the learning process, and teachers' perceptions of inclusive classes influence the quality of inclusive class implementation. For this reason, this research aims to analyse teachers' perceptions of implementing inclusive classes. This research was carried out using a survey method involving 285 teachers in Indonesia as respondents. The data in this study was collected using a questionnaire consisting of several closed and several open questions. The collected data was then analyzed quantitatively and qualitatively. Based on the quantitative data, this research found that teachers in Indonesia have positive perceptions of implementing inclusive classes. However, from the qualitative data, it was found that they still feel they need more knowledge to implement quality inclusive classes. Additionally, training regarding implementing inclusive classes is still very limited, so it has yet to make teachers feel confident in implementing inclusive classes. Thus, this study concludes that teachers in Indonesia positively perceive implementing inclusive classes but cannot implement them optimally. So, support from the government, especially the Ministry of Education, Culture, Research and Technology, to facilitate education and training in implementing inclusive classes for teachers is necessary to realize inclusive classes and quality inclusive education.